Three-Dimensional Finite Difference Analysis on the Ground-Sequential Tunneling-Superstructure Interaction - Ali Lakirouhani; Reyhaneh Jafari; Hadi Hasanzadehshooiili (Advances in Civil Engineering)
In this paper, a three-dimensional finite difference analysis is presented to investigate the interactive effects of sequential tunneling and the superstructure on the settlement profile of the ground. To simulate the practical sequential tunneling procedure, tunnel excavation is conducted in a step-by-step framework; tunnel excavation starts from the beginning of the model and is updated in a continuous manner, and the installation of the tunnel support system is done with a delay step compared to tunnel excavation. The numerical modeling accuracy is validated using the available analytical and numerical solutions for both two-dimensional and three-dimensional simplified cases. The well-validated modeling procedure is adopted to investigate effects of tunnel diameter, depth of tunneling, and number of superstructure stories on the profile of occurring settlements. Two cases of free-field and three-dimensional superstructural modeling are compared with regard to the effect of tunneling. In addition, the effect of tunneling advancement on the generation of excess structural forces and moments are studied as another important factor in the soil-tunneling-superstructure interaction problem. It is observed that, in the free-field case, with advancing the tunnel face, the longitudinal settlement profiles approach the steady-state condition and the maximum ground settlement tends to converge to a specific value, whereas as the tunnel passes under a structure, the settlement increases steadily as the tunnel progresses. There is a direct relationship between the depth and diameter of the tunnel and the settlement. In addition, the effect of the number of superstructure stories on the maximum settlement is more considerable compared to the free-field condition. According to the results, when the tunnel passes under 8-story and 12-story structures, the maximum settlement increases by 40% and 70%, respectively, compared to the free-field condition. It is also shown that tunneling-induced settlements result in the regeneration of structural forces.